Manajemen Kepala Sekolah dalam Meningkatkan Profesionalisme Guru Akidah Akhlak di MI Muhammadiyah Kartasura - Muhammad Irfan Irfan; Yusuf Rohmadi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2021)
Abstract This research was conducted to determine the principal's management in improving the professionalism of the akidah akhlak teachers at MI Muhammadiyah Kartasura and the inhibiting and supporting factors. This research approach uses a qualitative descriptive. The results of the study can be described as follows: 1. A teacher in order to increase his professionalism in carrying out his duties as a teacher, he must understand, master, and be skilled in using new learning resources. The role or efforts taken by the school principal in improving the professional competence of akidah akhlak teachers include the role of educator, manager, administrator, supervisor, and motivator. 2. The results of the inhibiting and supporting factors are: The inhibiting factor is the infrastructure and students while the supporting factor is the teachers who have a good educational background and there is good cooperation between teachers and fellow teachers, and teachers and principals. Keywords: Management, principals, professionalism